Pengaruh Masker terhadap Akne Vulgaris (Maskne) - Khoirunnisa A. Mokoagow; Marlyn. G. Kapantow; Herry E. J. Pandaleke (e-CliniC, 2024)
Abstract: During the Covid-19 pandemic, Indonesian people were required to wear masks during their daily activities that caused increased duration of wearing masks associated with increased incidence of acne vulgaris. This study aimed to determine the relationship between the use of masks and acne vulgaris (maskne). This was a literature review study. Sources of information were obtained from journals and research articles in Pubmed, Google Scholar, and the British Journal of Dermatology which discussed the relationship between mask use and maskne. The results obtained 10 literatures with a cross sectional design that fulfilled the inclusion and exclusion criteria. Review of the 10 literatures resulted in a relationship between the use of masks and the occurrence of mask-induced acne (maskne). The distribution of respondents based on the incidence of maskne was most common in women and the type of mask most often used was the surgical mask. The majority of respondents replaced their masks twice daily with duration of use for 4-8 hours. In conclusion, there is a relationship between the use of masks and the occurrence of maskne. Keywords: mask; acne vulgaris; maskne   Abstrak: Selama pandemi Covid-19 masyarakat Indonesia diwajibkan menggunakan masker selama melakukan kegiatan sehari-hari sehingga durasi penggunaan masker meningkat dan meningkatnya kejadian akne vulgaris. Penelitian ini bertujuan untuk mengetahui hubungan penggunaan masker dengan akne vulgaris melalui suatu literature review. Sumber informasi didapatkan melalui jurnal maupun artikel penelitian pada Pubmed, Google Scholar, dan British Journal of Dermatology yang membahas mengenai hubungan penggunaan masker dengan mask-induced acne (maskne). Hasil penelitian mendapatkan 10 literatur yang sesuai kriteria inklusi dan eksklusi dengan desain potong lintang. Kajian 10 literatur ini mendapatkan adanya hubungan penggunaan masker dengan kejadian maskne. Sebaran jumlah responden berdasarkan kejadian maskne paling banyak pada perempuan dan jenis masker yang paling sering digunakan ialah masker bedah. Didapatkan paling banyak mengganti masker dua kali sehari dengan penggunaan selama 4-8 jam. Simpulan penelitian ini ialah terdapat hubungan penggunaan masker dengan kejadian maskne. Kata kunci: penggunaan masker; akne vulgaris; maskne